Relationship of High-Sensitivity C- Reactive Protein (Hs-Crp) with the Components of Metabolic Syndrome - Amir, Mirza Md.; Rouf, Md Abdur; Hassan, Md Habib; Barua, Anupam (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Metabolic syndrome is associated with both the development of Hypertension, Diabetes Mellitus and an increased risk of adverse cardiovascular outcome. It is considered aspro inflamatory state linked with low grade systemic inflammation. C- reactive protein is a powerful biomarker of chronic systemic inflammation. Aim of this study is to evaluate the relationship of Highsensitivity C-reactive Protein (hs-CRP) with the components of Metabolic Syndrome (MetS) among hospitalized patients. Materials and methods: 50 patients of 18 years and above with metabolic syndrome, attending outdoor or admitted to Medicine Department of Chittagong Medical College Hospital from January 2016 to December 2016 were enrolled for this cross sectional study. The National Cholesterol Education Panel (NCEP) ATP – III, 2001 criteria was used for the diagnosis of MetS. Results: hsCRP level was found increased in almost every components of MetSin univariate analysis but the differences were not statistically significant. Patients with MetS had higher value of hs-CRP than without MetS (5.18±1.98 Vs 3.51± 1.63mg/l) with a p value 0.023. Conclusions: Patients with metabolic syndrome had higher levels of hs-CRP than those without metabolic syndrome and hs-CRP levels increased directly with increasing number of its components. JCMCTA 2020 ; 31 (1) : 71-75